Masyarakat Madura dalam Budaya Muy-Tamuyan (Tinjauan Fenomenologi Edmund Husserl) - Syazna Maulida; Zainal Arifin (Jurnal Tamaddun, 2022)
This article discusses how the Madurese community perceives one of the cultures found in Madura. Muy-tamuyan is considered the most important culture carried out by the Madurese community such as those in rural areas. This activity is growing rapidly in the Madurese community. As for the background of this research, it begins with how the enthusiastic attitude of the community in having Muy-tamuyan, talking until late, and the solidity that is built among other communities, this is the interest of researchers to investigate more deeply. Because, in addition to this culture is very important for the community, also because this culture is more than just a tradition because there are certain motives in it. In this article, the method used is a qualitative field method (field research) with a phenomenological approach to Edmund Husserl's theory. Sources of data obtained from interviews and literature studies are limited to matters that have relevance to this research. The findings in this study are that there are various perceptions of the Madurese community that make people very enthusiastic in carrying out this Muy-Tamuyan culture, including Muy-Tamuyan culture as a form of social solidarity, ukhwah Islamiyyah, and social interaction.